2017
DOI: 10.1038/s41598-017-16764-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human and mouse telomerase genes by genomic contexts and transcription factors during embryonic stem cell differentiation

Abstract: Differential regulation of telomerase reverse transcriptase (TERT) genes contribute to distinct aging and tumorigenic processes in humans and mice. To study TERT regulation, we generated mouse embryonic stem cell (ESC) lines containing single-copy bacterial artificial chromosome (BAC) reporters, covering hTERT and mTERT genes and their neighboring loci, via recombinase-mediated BAC targeting. ESC lines with chimeric BACs, in which two TERT promoters were swapped, were also generated. Using these chromatinized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Next, we determined whether the human genomic sequences conferred human-like TERT regulation in mouse cells. A subset of aforementioned BAC reporters were integrated into the same acceptor site in a mouse ESC line T2-5 by RMBT 11 . The TERT promoters in all the BAC reporters, M(wt), M(hPro), M(h5IR), M(h5IRI2), and M(h5IRI2I6), were highly active in ESCs as determined by ratios of Rluc / Fluc .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we determined whether the human genomic sequences conferred human-like TERT regulation in mouse cells. A subset of aforementioned BAC reporters were integrated into the same acceptor site in a mouse ESC line T2-5 by RMBT 11 . The TERT promoters in all the BAC reporters, M(wt), M(hPro), M(h5IR), M(h5IRI2), and M(h5IRI2I6), were highly active in ESCs as determined by ratios of Rluc / Fluc .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies revealed that the hTERT gene was embedded in a condensed chromatin domain in somatic cells and inhibition of histone deacetylation led to an opening of this domain and activated hTERT transcription 10 . We have recently shown that repression of the hTERT promoter was dictated by distal elements and required a human specific genomic context 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulation is essential for establishing and maintaining stem cell function, and evidence suggests that epigenetic dysregulation leads to potential changes in stem cells during aging [18] [25] [26] [27]. The term epigenetics refers to changes in gene expression that do not involve changes in the underlying DNA sequence [28] [29].…”
Section: Impact Of Stem Cell Senescence In Aging and Diseasesmentioning
confidence: 99%
“…It is well-known that substantial genes were regulated by transcription factors (TFs), recognized as the master regulators binding to DNA sequences specifically and thereby modulating gene transcription. The transcriptional regulation elicited by TFs is of importance to normal function of the organism, with transcriptional regulation central to cell cycle growth and survive (2), cell differentiation (3), cell adhesion (4) and cell homeostasis (5). However, TF failure leads to nearly 1/3 of human developmental diseases ascribed to TF misregulations (6,7).…”
Section: Introductionmentioning
confidence: 99%